STRES KERJA DAN KOMITMEN ORGANISASI DIPENGARUHI BERPIKIR POSITIF SERTA KEPUASAN KERJA - Farhansyah, Ifan; Sitepu, Adma Sari (POLITEKNIK LP3I JAKARTA, 2025)
High work pressure in the manufacturing sector has led to a decline in employee commit-ment to organizations. This study aims to analyze the effect of job stress on organizational commitment, with positive thinking and job satisfaction as moderating variables. The popu-lation of this research includes all production operators at a Japanese automotive foreign investment company in the MM2100 industrial area, Cikarang. A total of 280 respondents were selected using purposive sampling. This research uses a quantitative approach, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that job stress has a negative and significant effect on organization-al commitment. The higher the perceived stress, the lower the employee's commitment. Posi-tive thinking and job satisfaction are proven to weaken the negative effect of stress on com-mitment. Employees who maintain a positive mindset and are satisfied with their superiors and career development opportunities tend to be more resilient under pressure. This study suggests that management should create a healthy work environment, provide training on positive thinking, and establish a fair career development system. The findings contribute to human resource strategies, especially in reducing the impact of work stress on employee loyalty.